The Effect of a Nucleation Layer on Morphology and Grain Size in MOCVD-Grown β-Ga2O3 Thin Films on C-Plane Sapphire - Dimitrocenko, Lauris; Strikis, Gundars; Polyakov, Boris; Bikse, Liga; Oras, Sven; Butanovs, Edgars (MDPI, 2022)
β-Ga2O3 thin films grown on widely available c-plane sapphire substrates typically exhibit structural defects due to significant lattice and thermal expansion mismatch, which hinder the use of such films in electronic devices. In this work, we studied the impact of a nucleation layer on MOCVD-grown β-Ga2O3 thin film structure and morphology on a c-plane sapphire substrate. The structure and morphology of the films were investigated by X-ray diffraction, atomic force microscopy, transmission and scanning electron microscopy, while the composition was confirmed by X-ray photoelectron spectroscopy and micro-Raman spectroscopy. It was observed that the use of a nucleation layer significantly increases the grain size in the films in comparison to the films without, particularly in the samples in which H2O was used alongside O2 as the oxygen source for the nucleation layer growth. Our study demonstrates that a nucleation layer can play a critical role in obtaining high quality β-Ga2O3 thin films on c-plane sapphire. © 2022 by the authors. --//-- This is an open access article Dimitrocenko L., Strikis G., Polyakov B., Bikse L., Oras S., Butanovs E., "The Effect of a Nucleation Layer on Morphology and Grain Size in MOCVD-Grown β-Ga2O3 Thin Films on C-Plane Sapphire", (2022) Materials, 15 (23), art. no. 8362, DOI: 10.3390/ma15238362 published under the CC BY 4.0 licence.
This research is funded by the Latvian Council of Science project “Epitaxial Ga2O3 thin films as ultrawide bandgap topological transparent electrodes for ultraviolet optoelectronics” No. lzp-2020/1-0345. S.O. was supported by the European Union’s Horizon 2020 program, under Grant Agreement No. 856705 (ERA Chair “MATTER”). Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART².
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; gallium oxide; MOCVD; nucleation layer; thin films; UWBG materials